The Modern state in the Muslim world - Hammad, Muhammad (Al Khadim Research Journal of Islamic Culture and Civilization, 2022)
The goal of man has always been to enhance his social, economic, and political circumstances. He was able to discover better means of living in terms of food, shelter, and education through his tireless efforts. In diverse places of the world, the groundwork for a new set of culture and civilisation was gradually laid. Some of the greatest men who transformed social conventions and developed significant ethical, political, and philosophical ideals of life came from Babylonia, Assyria, Greece, India, and China. Plato and Aristotle stood out among them. Plato’s Republic and Aristotle’s Politics hold sway among the political treatises. The Greek intellectuals left behind their heritage of political organisation in a scientific form and imagined citizen rights as well as the moral and just ideals with felicity of expression. Among contemporary political theorists, Rousseau stands out for having beautifully articulated his thesis of the "social contract." The assumptions that are made when Islamic law and international human rights law are mentioned in the same sentence or title can differ. Some people can interpret that juxtaposition as an attempt to oppose current Islamic law norms in the human rights agendas’ interest. Others might detect an implied message in the juxtaposition aim to maintain Muslim colonial subjugation to the global North portions of the South. Others, however, might perceive a qualification of any assertion of truth or desire for a universally understood language.